Platelet activation favours NOX2-Mediated muscle damage in elite athletes: The role of cocoa-derived polyphenols - D'Amico, A.; Cavarretta, E.; Fossati, C.; Borrione, P.; Pigozzi, F.; Frati, G.; Sciarretta, S.; Costa, V.; De Grandis, F.; Nigro, A.; Peruzzi, M.; Miraldi, F.; et al. (Nutrients, 2022)
Mechanisms of exercise-induced muscle injury with etiopathogenesis and its consequences have been described; however, the impact of different intensities of exercise on the mechanisms of muscular injury development is not well understood. The aim of this study was to exploit the relationship between platelet activation, oxidative stress and muscular injuries induced by physical exercise in elite football players compared to amateur athletes. Oxidant/antioxidant status, platelet activation and markers of muscle damage were evaluated in 23 elite football players and 23 amateur athletes. Compared to amateurs, elite football players showed lower antioxidant capacity and higher oxidative stress paralleled by increased platelet activation and muscle damage markers. Simple linear regression analysis showed that sNOX2-dp and H2O2, sCD40L and PDGF-bb were associated with a significant increase in muscle damage biomarkers. In vitro studies also showed that plasma obtained from elite athletes increased oxidative stress and muscle damage in human skeletal muscle myoblasts cell line compared to amateurs` plasma, an effect blunted by the NOX2 inhibitor or by the cell treatment with cocoa-derived polyphenols. These results indicate that platelet activation increased muscular injuries induced by oxidative stress. Moreover, NOX2 inhibition and polyphenol extracts treatment positively modulates redox status and reduce exercise-induced muscular injury.